Frustrated Magnetism in Mott Insulating (V_{1−x}Cr_{x})_{2}O_{3} - J. C. Leiner; H. O. Jeschke; R. Valentí; S. Zhang; A. T. Savici; J. Y. Y. Lin; M. B. Stone; M. D. Lumsden; Jiawang Hong; O. Delaire; Wei Bao; C. L. Broholm (Physical Review X, 2019)
V_{2}O_{3} famously features all four combinations of paramagnetic versus antiferromagnetic and metallic versus insulating states of matter in response to percent-level doping, pressure in the GPa range, and temperature below 300 K. Using time-of-flight neutron spectroscopy combined with density functional theory calculations of magnetic interactions, we have mapped and analyzed the inelastic magnetic neutron scattering cross section over a wide range of energy and momentum transfer in the chromium-stabilized antiferromagnetic and paramagnetic insulating phases. Our results reveal an important magnetic frustration and degeneracy of the paramagnetic insulating phase which is relieved by the rhombohedral-to-monoclinic transition at T_{N}=185  K. This leads to the recognition that magnetic frustration is an inherent property of the paramagnetic phase in (V_{1−x}Cr_{x})_{2}O_{3} and plays a key role in suppressing the magnetic long-range-ordering temperature and exposing a large phase space for the paramagnetic Mott metal-insulator transition to occur.